ANALYSING THE CREDIBILITY OF META-GEOPOLITICAL FRAMEWORK: IMPLICATIONS OF KINDLEBERGER TRAP ON CHINA (POST-BRI) (Margalla Papers, 2022)
The world had to suffer the implications of Kindleberger Trap in post-World War I due to the vacuum created at the international level to provide global public goods by the then superpowers – Great Britain and the US. The exact implications could be faced by the rest of the world in the 21st century. Today, China aspires to become a global leader; thus, it must avoid the Kindleberger Trap, which can cause inferences for its stability. For this purpose, the state must provide the world with global public goods as a responsibility. The US had this responsibility until the Trump administration enacted the policy of isolation, just like the post-World War I era. This policy of the US administration created a gap at the international level that China wants to fill as a global power. This paper, therefore, examines the implications of the Kindleberger Trap on China, particularly after the initiation of China’s Belt and Road Initiative. Meta-geopolitics is used as a framework to highlight areas of China’s strength along with rooms that can cause a setback for China’s stability at the national and international levels. This paper also analyses the domestic policies of China and how to avoid the Kindleberger Trap. Bibliography EntryTariq, Ramsha, and Aiysha Safdar Ali. 2022. "Analysing the Credibility of Meta-Geopolitical Framework: Implications of Kindleberger Trap on China (Post-BRI)." Margalla Papers 26 (2): 72-86.